The Beauty Bible - Stacey, Sarah and Fairley, Josephine (London House of Fraser, 1996)
The authors bring together everything a woman needs to know to look her best from head to toe. The text covers make up and massage, skin care and stress management, hair care and weight control, health supplements and all forms of pampering, beating cellulite and eating for energy and beauty.
Include Color Illustration and Index
Keywords: Beauty, Personal -- Aging--Prevention -- Women--Health and hygiene